Application of Heparin/Collagen‐REDV Selective Active Interface on ePTFE Films to Enhance Endothelialization and Anticoagulation. Issue 8 (18th April 2018) - Shan, Yaping; Jia, Bing; Ye, Ming; Shen, Hua; Chen, Weicheng; Zhang, Huifeng
Abstract: Expanded polytetrafluoroethylene (ePTFE) prosthetic valves have been widely used in clinical applications in Asian countries. However, these valves still have limits with regard to thrombosis, neointimal hyperplasia, restenosis, and valvar vegetation. The achievement of in situ endothelialization on implant materials is a promising way to overcome those limits. Here, heparin/collagen multilayers were fabricated on ePTFE films via a layer‐by‐layer (LBL) self‐assembly technique, and then, the endothelial cell (EC) adhesive peptide sequence Arg‐Glu‐Asp‐Val (REDV) was immobilized on the multilayers. After modification with the heparin/collagen multilayers with or without REDV peptide, less platelet activation and aggregation were observed, the blood coagulation time was increased, and the hemolysis rate was decreased compared to that on pristine ePTFE films. The REDV‐functionalized ePTFE films positively impacted early EC adhesion, later cell proliferation and cell activity. The EC barrier was confirmed to be successfully achieved on the functionalized ePTFE film surface in vitro. The successful assembly of the REDV‐functionalized heparin/collagen multilayer on ePTFE films improved the blood compatibility, anticoagulant properties, and cell compatibility of the films in vitro, and thus, represents a candidate approach for applications requiring quick in situ endothelialization in vivo.